(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The current airline industry of India has passed through so many changes like the standardization of airports, emergence of low cost carriers, privatization of airline industry in India and increase in the affordability of airline service among Indians. The present study is an attempt to analyze the operating efficiency of two scheduled domestic airlines i.e. Air India and Indigo Airlines. The study is based on secondary data collected from the Profit and Loss Ac and Balance Sheet associated with schedules, annexure available in the published annual reports of airlines and Capitaline data base. The data have been collected for the past twelve years ranging from 2004-05 to 2015-16 and compiled into tables and analyzed with the help of Ratio Analysis, Mean, Standard Deviation, Co-efficient of Variation and Compound Annual Growth Rate. It has been found in the present that the national carrier i.e. Air India could not earn profits during the entire study period. The result conducted on the expenses ratio and profitability ratio depicts that the operating efficiency as well as profitability of Air India has been poor during the study period. On the other hand, the financial performance of private carrier i.e. Indigo Airlines has been good as compared to Air India which is clearly depicted in the ratio analysis.